Atomistic Modeling‐Based Design of Novel Materials1 . Issue 4 (10th January 2017) - Holec, David; Zhou, Liangcai; Riedl, Helmut; Koller, Christian M.; Mayrhofer, Paul H.; Friák, Martin; Šob, Mojmír; Körmann, Fritz; Neugebauer, Jörg; Music, Denis; Hartmann, Markus A.; Fischer, Franz D.
Abstract : Modern materials science increasingly advances via a knowledge‐based development rather than a trial‐and‐error procedure. Gathering large amounts of data and getting deep understanding of non‐trivial relationships between synthesis of materials, their structure and properties is experimentally a tedious work. Here, theoretical modeling plays a vital role. In this review paper we briefly introduce modeling approaches employed in materials science, their principles and fields of application. We then focus on atomistic modeling methods, mostly quantum mechanical ones but also Monte Carlo and classical molecular dynamics, to demonstrate their practical use on selected examples. Abstract : This review demonstrates an application of atomistic modeling to current materials science problems . As an example, atomic structure of a cubic TiN–AlN solid solution is overlaid with its electronic charge density determining type and strength of bonding, and consequently its physical properties.